Through Their Own Eyes: The Implications of COVID-19 for PhD Students. Issue 1 (23rd November 2022) - Haas, Nicholas; Gureghian, Aida; Jusino Díaz, Cristel; Williams, Abby
Abstract: COVID-19 is expected to radically alter higher education in the United States and to further limit the availability of tenure-track academic positions. How has the pandemic and its associated fallout affected doctoral students' career aspirations and priorities? We investigate this question by comparing responses to a PhD career survey prior to and following significant developments in the pandemic. We find little evidence that the pandemic caused substantial shifts in PhD students' aspirations and priorities. However, some differences emerge when considering later dates in our survey period, particularly among more senior students who express a greater interest in some non-academic careers and job characteristics. Contrary to expectation, we also find evidence that the pandemic improved some students' perceptions of their academic departments. In our conclusion, we speculate whether steps taken by the comparatively well-resourced institution that we study helped to mitigate some of the more negative consequences of the pandemic.